Epicardium-derived cells: a new source of regenerative capacity. - Vieira, J; Riley, P (2011)
Cardiovascular regenerative medicine aims to counter muscle loss post ischaemic disease with the identification of new cellular sources for cardiomyocyte replacement. A number of embryonic and adult cell models have been explored preclinically and in patient trials, but modest outcome, coupled with issues with impaired graft survival and limited/immature (trans-) differentiation alongside host rejection, has left the door open for more therapeutically efficacious sources of myocardial regeneration. Due to its fundamental role in heart development, the epicardium emerges as an obvious candidate. Here, recent findings are reviewed that show adult epicardium-derived cells as a new source of regenerative capacity for heart repair.